Does plant-based milk reduce sales of dairy milk? Evidence from the almond milk craze. (3rd April 2023) - Slade, Peter
Abstract: In recent years, there has been significant growth in the sales of plant-based alternatives to meat and dairy products. However, it remains unclear whether these alternatives are actually reducing sales of livestock-derived products. This paper examines the relationship between the sales of one particular livestock-derived product – unflavored dairy milk – and its plant-based alternative – nondairy milk. Using data from a panel of US consumers between 2004 and 2018, I find that a 1-gallon increase in nondairy milk sales is associated with a 0.43–0.60 gallon reduction in dairy milk sales. The inverse relationship between dairy and nondairy milk purchases is strongest among households with high initial expenditure on dairy milk. Despite the inverse relationship between dairy and nondairy milk purchases, the rapid increase in nondairy milk sales between 2009 and 2018 explains little of the concomitant decline in dairy milk sales.